2005
DOI: 10.1021/jo050811r
|View full text |Cite
|
Sign up to set email alerts
|

Nitroso Group Transfer in S-Nitrosocysteine:  Evidence of a New Decomposition Pathway for Nitrosothiols

Abstract: The rate of S-nitrosocysteine decomposition in a pH range between 0.7 < pH < 13 exhibits first- and second-order dependence on total cysteine concentration. The second-order term is only observed for pH values between 6.9 < pH < 12. Both first- and second-order terms show a complex dependence on the acidity of the medium. They increase with increasing pH, reaching a maximum value around pH = 8 and then decrease with further increase in pH. An analysis of the reaction products reveals the absence of nitrite ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 33 publications
0
18
0
1
Order By: Relevance
“…In the current study, our aim was to determine the differences in nitrosamine formation in red meat and in red meat in the stomach between nitrite, Cys-SNO, and NAC-SNO as possible meat-curing agents. We show RSNO containing primary amines can efficiently deliver reactive nitrogen species to secondary amines to generate carcinogenic N-NA by the S- to N-transnitrosation-decomposition pathway of RSNO . These results suggest that a primary amine in RSNO molecules has a major influence on nitrosamine formation.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…In the current study, our aim was to determine the differences in nitrosamine formation in red meat and in red meat in the stomach between nitrite, Cys-SNO, and NAC-SNO as possible meat-curing agents. We show RSNO containing primary amines can efficiently deliver reactive nitrogen species to secondary amines to generate carcinogenic N-NA by the S- to N-transnitrosation-decomposition pathway of RSNO . These results suggest that a primary amine in RSNO molecules has a major influence on nitrosamine formation.…”
Section: Introductionmentioning
confidence: 75%
“…The reaction is facilitated by the presence of additional l -Cys that acts as a binucleophile. In this regard, Adam et al demonstrated a linear dependence of the reaction rate constant k obs to decomposition of Cys-SNO in the presence of elevated concentrations of free cysteine. This amino acid facilitated the S- to N-transnitrosation of Cys-SNO, forming reactive nitrogen species, carbon center radicals, and releasing nitrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Typical examples are the O-NOǞN-NO migrations observed in the nitrosation of amides and ureas, [14] amino acids [15] in acidic media, and hydroxylamines; [16] the C-NOǞN-NO migrations found in the nitrosation of indoles [17] in acidic media; and the N-NOǞC-NO migrations observed in the Fischer-Hepp rearrangement. [18] Also, S-NOǞN-NO migrations are common when studying nitrosation of cysteine in acidic [19] and basic or neutral [20] media, thioureas [21] and thioproline or thiomorpholine. [22] Scheme 4.…”
Section: Resultsmentioning
confidence: 99%
“…It is widely reported that S-nitrosothiols are stabilized under acidic conditions. [60][61][62] (see Fig. S4 in ESI † for a detailed explanation.)…”
Section: Nitric Oxide Releasementioning
confidence: 99%